Dry sliding and tribocorrosion behaviour of hot pressed CoCrMo biomedical alloy as compared with the cast CoCrMo and Ti6Al4V alloys - Doni, Z. (2013)
Alternative processing routes are being widely studied for biomedical implant materials. Hot pressing (HP) is a powder metallurgy (P/M) process that combines the pressing and sintering steps simultaneously and therefore, provides a simpler production route with further advantages. However, dry sliding and tribocorrosion behaviour of HP CoCrMo alloy is yet to be studied. Since the implants are exposed to wear stresses and corrosive environments during their lifetime, tribocorrosion is an important issue for the implant materials. Thus, the present work aims at evaluating the dry sliding and tribocorrosion behavior of the HP CoCrMo implant material as compared with the widely used commercial cast Ti6Al4V and CoCrMo implant materials. All tribological experiments were carried out under 1 N normal load, 1 Hz frequency and 3 mm total stroke length, using a reciprocating ball-on-plate tribometer. Tribocorrosion experiments were performed at both room and the body temperatures, in 8 g/l NaCl solution. Open circuit potential (OCP) was measured before, during and after sliding. Worn surfaces investigated by field emission gun scanning electron microscope (FEG-SEM) equipped with energy dispersive X-ray spectroscopy (EDS), and the wear rates were calculated using a profilometer. Results suggest that all PHCoCrMo samples presented better wear resistance after both dry sliding and tribocorrosion tests. Additionally, as compared to the cast CoCrMo samples, HP CoCrMo samples presented better wear resistance in dry sliding conditions and similar wear resistance in tribocorrosion conditions. Due to the experimental results, it may be suggested that HP can be considered as a simple and low cost alternative production route for CoCrMo implant materials.